IDENTIFICATION OF FLOOD-PRONE AREAS IN THE LOWER CILIWUNG WATERSHED BASED ON GEOGRAPHIC INFORMATION SYSTEMS - Alyssa, Hana; Setiawan, Cahyadi; Mataburu, Ilham Badaruddin (Universitas Negeri Surabaya, 2025)
Given the geographical reality of, a significant contributor to the city's recurrent flooding is the inherent presence of rivers within the region, including the Ciliwung River. This study aims to map areas vulnerable to flooding in the Ciliwung Hilir Watershed. The flood-prone area map produced from Composite Mapping Analysis and overlay through a Geographic Information System’s based on parameters such as soil type, land elevation, slope gradient, land use, rainfall, and river density. From the processed data, the flood-prone areas in the Ciliwung Hilir Watershed are classified into three levels of vulnerability: low 296.83 Ha (3.13%), moderate 2,610.03 Ha (27.5%), and high 6,585.21 Ha (69.37%). The map has a very high accuracy of 88.8%, based on validation data from flood occurrences in DKI Jakarta from 2010 to 2020. The generated flood vulnerability map will provide predictive insights, supporting the implementation of mitigation strategies designed to minimize potential adverse impacts. Keywords: Composite Mapping Analysis, Lower Ciliwung Watershed, Flood Vulnerability